2005
DOI: 10.1063/1.1862761
|View full text |Cite
|
Sign up to set email alerts
|

Decay of ferroelectric domains formed in the field of an atomic force microscope

Abstract: Ferroelectric domains formed in the electric field of an atomic force microscope decay with time when the reversal voltage is removed. We propose a theory for this process. Dynamic equations describing the time evolution of the domain sizes are constructed and solved. It is shown that the larger the domains, the more stable they are. The time dependences of the domain length and base radius are qualitatively different. The radius of the domain decreases during the decay process, and for a large domain there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…According to a recently published theory, ferroelectric domains may be stable for several years even in defect-free barium titanate crystal, if their radius exceeds the critical value of around ϳ1 m. 20 It was also found that string-like domains tailored in RbTiOPO 4 and LiNbO 3 crystals using the HVAFM were stable for at least several months. 16,17 However, the domain decay process may be accelerated by increasing the probability for domain walls depinning, done, for example, by heating the sample.…”
Section: Direct Observation Of Pinning Centers In Ferroelectricsmentioning
confidence: 95%
“…According to a recently published theory, ferroelectric domains may be stable for several years even in defect-free barium titanate crystal, if their radius exceeds the critical value of around ϳ1 m. 20 It was also found that string-like domains tailored in RbTiOPO 4 and LiNbO 3 crystals using the HVAFM were stable for at least several months. 16,17 However, the domain decay process may be accelerated by increasing the probability for domain walls depinning, done, for example, by heating the sample.…”
Section: Direct Observation Of Pinning Centers In Ferroelectricsmentioning
confidence: 95%
“…The thermodynamics of domain formation in the tip field has been extensively studies for uniaxial [31,32,33,34,35,36,37,38] and multiaxial [39] ferroelectrics in the rigid ferroelectric approximation. The kinetics of this process was studied by Molotskii et al [40,41]. Recently, a number of studies of thermodynamics of domain formation in the phase-field approximation were reported [17,30,42,43,44].…”
Section: Introductionmentioning
confidence: 99%
“…These results are in good agreement with the calculated critical radius for domain stability in BTO of 74-100 nm. 22 Note that the formation of domains by ferroelectric domain breakdown is not favorable in BTO crystals due to the high dielectric constant of BTO. 22 Domains fabricated in this study with Ϫ10 and Ϫ20 V pulses decayed rapidly from initial radii of ϳ250 nm and 500 nm, respectively, and while larger domains were more stable, they became smaller after scanning with ac bias overnight.…”
mentioning
confidence: 99%
“…22 Note that the formation of domains by ferroelectric domain breakdown is not favorable in BTO crystals due to the high dielectric constant of BTO. 22 Domains fabricated in this study with Ϫ10 and Ϫ20 V pulses decayed rapidly from initial radii of ϳ250 nm and 500 nm, respectively, and while larger domains were more stable, they became smaller after scanning with ac bias overnight. That these domains decayed despite surpassing the critical radius range suggests an incomplete polarization screening of the switched domains on their polar surfaces ͑assuming that the domains extend through the whole sample thickness͒.…”
mentioning
confidence: 99%
See 1 more Smart Citation